2015
DOI: 10.1111/ejh.12645
|View full text |Cite
|
Sign up to set email alerts
|

Non‐anaemic iron deficiency – a disease looking for recognition of diagnosis: a systematic review

Abstract: There is emerging evidence that NAID is a disease in its own right, deserving of further research in the development of strategies for detection and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 60 publications
1
83
0
1
Order By: Relevance
“…Iron deficiency with or without anaemia, is associated with maternal fatigue (Lee & Zaffke, 1999;Pratt & Khan, 2016) and, potentially, poorer quality of life and increased risk of postpartum depression (Corwin et al, 2003). A recent systematic review of non-anaemic iron deficiency found that fatigue improves with iron replacement (Pratt & Khan, 2016), although there was only one randomised control trial and one other relevant study. Altered thyroid metabolism can also occur in iron deficiency anaemia (lower thyroidstimulating hormone and T3 hormone) and contribute to fatigue (Beard et al, 1989(Beard et al, , 1990.…”
Section: Maternal Morbidity and Mortalitymentioning
confidence: 99%
“…Iron deficiency with or without anaemia, is associated with maternal fatigue (Lee & Zaffke, 1999;Pratt & Khan, 2016) and, potentially, poorer quality of life and increased risk of postpartum depression (Corwin et al, 2003). A recent systematic review of non-anaemic iron deficiency found that fatigue improves with iron replacement (Pratt & Khan, 2016), although there was only one randomised control trial and one other relevant study. Altered thyroid metabolism can also occur in iron deficiency anaemia (lower thyroidstimulating hormone and T3 hormone) and contribute to fatigue (Beard et al, 1989(Beard et al, , 1990.…”
Section: Maternal Morbidity and Mortalitymentioning
confidence: 99%
“…31 Where iron deficiency is discussed, it is frequently perceived as the most common nutritional disorder worldwide, [31][32][33] but not as a medical condition in and of itself. 34 It is clear that the heterogeneity in how iron deficiency is defined is a knowledge gap that is compounding physicians' lack of confidence in recognizing and diagnosing this condition. The lack of a standard simple definition for iron deficiency hinders its uncoupling from iron deficiency anemia and its acceptance as a standalone medical condition with distinct clinical implications.…”
Section: Defining Iron Deficiencymentioning
confidence: 99%
“…Blood collectors recruit and draw adolescents who are iron replete or have NAID; occasionally, some eligible teenagers develop post‐donation IDA. In non‐donors, measures of educational attainment in NAID relative to iron replete individuals for both language and mathematics skills have not been shown to be statistically significantly different (Pratt & Khan, ). Despite inconclusive results examining effects of NAID on adolescent cognition, this is a period of significant brain development involving the myelination of important cortical association areas.…”
Section: Adverse Effects Of Iron Depletionmentioning
confidence: 99%